Compositional changes in cell wall polysaccharides from apple fruit callus cultures modulated by different plant growth regulators - Alayón Luaces, Paula (2012)
The cell wall composition of apples callus cultures showed changes in the presence of 5 mg l−1 of three different plant growth regulators (PGRs), namely picloram, abscisic acid and gibberellic acid. Although the structural functions of cell walls do not generally allow for pronounced variations of the total pectin and matrix glycan content, this work provides evidence that the addition of these plant growth regulators can rule, at least partly, cell wall metabolism in apple callus cultures. The chelator- and carbonate-extracts always had the analytical characteristics of pectins, with high proportions of uronic acids, arabinose and galactose as the main monosaccharides, and a significant proportion of rhamnose, but the cross-linking glycan fractions were still rich in RG-I-like material. The application of PGRs produced shifts of uronic acid and neutral sugars between fractions. Arabinose was the neutral sugar exhibiting more variations in apple callus cell wall. Picloram and abscisic acid produced an increase of the uronic acid contents of the cell walls. The AIRs obtained from calluses treated with different PGRs did not show large amounts of high molecular weight products, as determined by size-exclusion chromatography. For the carbonate-extract only the callus treated with picloram displayed two separated peaks for products of different molecular weights. The chromatographic profiles for the 4% KOH-extract displayed two peaks for all the treatments, one very sharp with high molecular weight, and another one wider of smaller molecular weight, whereas the difference between treatments can only be appraised through the areas of the peaks. This is the first report on cell wall composition from fruit calluses supplemented with different PGRs.